Konsep Wasiat Menurut Hukum Islam, Kompilasi Hukum Islam, dan KUH Perdata. - Achmad Fauzi Imron (Asy-Syari’ah : Jurnal Hukum Islam, 2015)
The title of this research is Konsep Wasiat Menurut Hukum Islam, Kompilasi Hukum Islam, dan KUH Perdata, in a context of interpretation blurring testament exist in Islamic law and the Civil Code. Besides, there are similarities, there are also differences that characterize testament stipulated in the legal system. People consider differences arising merely written and not written a will. So as to overcome the fuzziness interpretation, it is necessary to determine the characteristics of a comparison with the limitedly. Therefore, the comparison is useful for the formation of the national inheritance law other than Islamic law and the Civil Code, also compared with the compilation of Islamic law as a positive law in force in the Islamic Religious Court. This can be formulated in several issues, namely how to draft a will according to Islamic law, Compilation of Islamic Law, and the Civil Code as well as what the similarities and differences that exist in Islamic Law, Compilation of Islamic Law and the Civil Code. This research includes the study of literature / literary called normative legal research using a qualitative approach. Method of data collection is done by the method of documentation and comparative descriptive analysis. Probate in Islamic law has pillars and conditions attached to the pillars, namely the musyi, mshalahu, mushabihi and shighat. Probate property is limited and can be canceled 1/3. According to KHI, harmonious testament that people who intestate, the recipient will, objects diwasiatkan and shighat will. Probate property is limited and can be canceled 1/3. Meanwhile, according to the Civil Code of the conditions is no pewasiat, the recipient will, diwasiatkan objects, as well as the editor of a will. Forms of wills that openbaar testament, testament olografis, and testament closed. The contents of a will can be erftelling and legaat. Similarities between testament according to Islamic law, KHI and the Civil Code which is done after death, probate limits equally should not be detrimental to the heirs, but in different terms (ie 1/3 and legitime portie) as well as the cancellation of the will. While the difference lies in the harmony and the terms of a will. Shape will that in Islamic law made orally and in writing, KHI can be done verbally / in writing / before a notary and in the Civil Code in the form of a deed notarized. Prominent difference lies in the content of the will in the Civil Code that is not known in Islamic law and KHI. As a result of the law is closely related to the acceptance of the will is a person who receives a will has the right to own property or not (canceled his will).